An innovative hollow fiber vacuum membrane distillation-crystallization (VMDC) coupling process for dye house effluent separation to reclaim fresh water and salts. (20th February 2022) - Shi, Wenying; Li, Tengfei; Tian, Yin; Li, Hongbin; Fan, Mengjie; Zhang, Haixia; Qin, Xiaohong
Abstract: The discharge of dyeing wastewater has become one of the important restrictive factors for the green manufacturing and sustainable development of textile industry. Realizing the maximum reuse of dyeing wastewater resources is an efficient solution. Vacuum membrane distillation crystallization (VMDC) coupling process can separate and recover the components such as fresh water and salts (mordants) in dyeing wastewater as well as achieve the concentration of the valuable substances (dyes) simultaneously. In this study, hollow fiber VMDC coupling process was developed for the treatment of saline dye solution to recover the inorganic salt (mordant Al(NO3 )3 ) and fresh water while realize the high-multiple concentration of dyes (Congo red, CR). High-performance hydrophobic PVDF hollow fiber porous membrane was prepared by the dry-jet wet-spinning technique and used in the VMDC process. The VMDC process in one cycle was optimized, including MD section, crystallization and membrane cleaning process. Variations of MD separation performance including permeate water flux and solute rejection of PVDF hollow fiber membrane for CR and Al(NO3 )3 with operating time was determined by the vacuum membrane distillation (VMD) experiment. A three-cycle VMDC process was developed and the variations of MD separation performance and crystal yield in each VMDC cycle were investigated. In each VMDC process, the rejection of CR and Al (NO3 ) 3 by hollow fiber MD can be maintained above 99%. With the extension of VMDC operating time, the gradually decreased water flux can be recovered by around 90% through the combined cleaning method of NaOH and absolute ethanol (abs). In the three-cycle of VMDC process, 42.5, 32.5 and 9.8% of water were recovered from the feed solution with a total recovery ratio of 84.8%. In the second and third VMDC cycles, 48.0 and 21.5% of the salts in the saline dye solution were obtained with a total salt recovery ratio of 69.5%. An estimation of economic cost was also made to evaluate the economic feasibility of the proposed MDC process for its practical application. Hollow fiber VMDC coupling process was proved to be a simultaneously efficient separation method of saline dye solution. Graphical abstract: Image 1 Highlights: Hollow fiber VMDC coupling process was developed for the treatment of saline dye solution. A three-cycle VMDC coupling process was designed for continuous highly efficient separation. Total salt recovery ratio and water recovery ratio can reach 69.5% and 84.8%, respectively. Dyes can be concentrated to 6.5 times the initial concentration.